2013
DOI: 10.1039/c3sm51094h
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical analysis of the thermodynamics of 2D cluster formation of 2-hydroxycarboxylic acids at the air/water interface

Abstract: In the framework of the quantum chemical semiempirical PM3 method, the thermodynamic and structural parameters of formation and clusterization were calculated for 2-hydroxycarboxylic acids with the general formula C n H 2n+1 CHOHCOOH (n ¼ 5-15). Dimers and tetramers were formed on the basis of optimized monomer structures. It was shown that the alkyl chains in the considered associates orientate themselves with the following values of the tilt angles with respect to the pand q-directions of the interface: d ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 47 publications
5
37
0
1
Order By: Relevance
“…As in our previous works the calculation of the structural and thermodynamic parameters of clusterization of monoethoxylated alcohols at the air/water interface has been carried out using the quantum chemical program package MOPAC2000 64 in the framework of the semiempirical PM3 method. This method has been successfully used for the assessment of the clusterization thermodynamic parameters of ten homologous series of surfactants [51][52][53][54][55][56][57][58][59][60][61] and of the geometric parameters of monolayers for aliphatic alcohols, 63 saturated, 61 unsaturated, 55,59 and a-substituted 57,58,62 carboxylic acids.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our previous works the calculation of the structural and thermodynamic parameters of clusterization of monoethoxylated alcohols at the air/water interface has been carried out using the quantum chemical program package MOPAC2000 64 in the framework of the semiempirical PM3 method. This method has been successfully used for the assessment of the clusterization thermodynamic parameters of ten homologous series of surfactants [51][52][53][54][55][56][57][58][59][60][61] and of the geometric parameters of monolayers for aliphatic alcohols, 63 saturated, 61 unsaturated, 55,59 and a-substituted 57,58,62 carboxylic acids.…”
Section: Model and Methodsmentioning
confidence: 99%
“…As indicated by previous studies, 31,37,38,49 the form and structure of C n E m domains varies depending on the temperature and alkyl chain length of molecules. Therefore it can be assumed that monoethoxylated alcohols likely form monolayers with structures similar to the structure of aliphatic alcohols, which are adequately described using the quantum chemical model [50][51][52][53][54][55][56][57][58][59][60][61][62] in a recent paper. 63 Therefore, the objective of the present work is to investigate the structural parameters of the hexagonal monolayers of monoethoxylated alcohols with normal structure at the air/water interface and to calculate thermodynamic parameters of clusterization for such monolayers using the quantum chemical semiempirical PM3 method.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 However, there are few theoretical papers modeling their behavior during monolayer formation. Therefore, we developed an approach for the description of 2D clusterization of nonionic surfactants (aliphatic alcohols, 19,20 carboxylic acids, 21,22 amides, 23 α-substituted carboxylic acids, 24,25 and so on) at the air/water interface. The values obtained for the calculated alkyl chain length of the surfactants enabling monolayer formation at a given temperature are in agreement with the existing experiments and values of the structural parameters of the corresponding monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…While during the formation of an oblique monolayer LE-LC phase transition occurs on the basis of surfactant dimers. 21 This is schematically illustrated in Figs. 1 and 2 by the example of aliphatic alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the available experimental data on the considered surfactant classes 19,21,31,34,36,42,[44][45][46] have shown that for monolayers with a hexagonal unit cell m≈3, and for films with oblique one -m≈2, with the exception for disubstituted melamine, for which this phase transition realizes on the basis of monomers. This is quite understandable, since the dialkyl-substituted melamine molecule itself has two hydrocarbon chains, participating in the formation of intramolecular CH•••HC interactions.…”
Section: Thermodynamic Parameters Of Surfactant Associatesmentioning
confidence: 99%